Exploring causal associations between plasma metabolites and attention-deficit/hyperactivity disorder - Shangyun Shi; Ancha Baranova; Hongbao Cao; Fuquan Zhang (BMC Psychiatry)
Abstract Background Observational studies reported altered levels of plasma metabolites in attention-deficit/hyperactivity disorder (ADHD). We aim to explore the causal link between plasma metabolites and ADHD. Methods We utilized Mendelian randomization (MR) analysis to assess the causal relationship between plasma metabolites and ADHD and the Genome-wide association study (GWAS) summary datasets were sourced from public databases. GWAS summary datasets were used in the study, including ADHD (n = 292,548) and 871 plasma metabolites (n = 8,299). Moreover, we used DrugBank and ChEMBL to evaluate whether the identified metabolites are potential therapeutic targets, and in addition, Bayesian colocalization analyses were conducted to assess the shared genetic signals between these metabolites and ADHD. Results Our MR analysis identified 20 plasma metabolites that conferred protective effects against the risk of ADHD, including dimethylglycine, 3-methoxytyramine sulfate, and adenosine 3’,5’-cyclic monophosphate (OR: 0.97–0.98). Additionally, 22 metabolites were associated with an increased risk of ADHD, including N-acetylneuraminate and 3-indoleglyoxylic acid (OR:1.01–1.03). Druggability evaluation showed that 12 of the ADHD-related metabolites have been targeted by pharmacological interventions. For example, doconexent has been used to increase the levels of docosahexaenoic acid. Our reverse MR analysis showed that genetic liability to ADHD may affect the abundance of 91 metabolites. Notably, several plasma metabolites had bidirectional causal associations with ADHD, including docosahexaenoate (DHA; 22:6n3), docosatrienoate (22:3n3), N1-methyladenosine, S-adenosylhomocysteine, and 4-allylcatechol sulfate. Conclusions Our study supported a causal role of plasma metabolites in the susceptibility to ADHD, and the identified metabolites may provide a new avenue for the prevention and treatment of ADHD. Clinical trial number Not applicable.